2016
DOI: 10.1186/s12864-016-2958-x
|View full text |Cite
|
Sign up to set email alerts
|

The beagle dog MicroRNA tissue atlas: identifying translatable biomarkers of organ toxicity

Abstract: BackgroundMicroRNAs (miRNA) are varied in length, under 25 nucleotides, single-stranded noncoding RNA that regulate post-transcriptional gene expression via translational repression or mRNA degradation. Elevated levels of miRNAs can be detected in systemic circulation after tissue injury, suggesting that miRNAs are released following cellular damage. Because of their remarkable stability, ease of detection in biofluids, and tissue specific expression patterns, miRNAs have the potential to be specific biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 62 publications
(71 reference statements)
2
64
0
Order By: Relevance
“…In vivo , miR‐122 makes up ~70% of the miRNA content in the liver, where it has been found to be involved in liver development, lipid metabolism and hepatitis C viral infection . Preclinical data have demonstrated that high miR‐122 elevations are observed in rodents given acetaminophen and beagle dogs given proprietary hepatotoxicants . This observation has been recapitulated in human studies.…”
Section: Promising New Dili Biomarkersmentioning
confidence: 87%
See 2 more Smart Citations
“…In vivo , miR‐122 makes up ~70% of the miRNA content in the liver, where it has been found to be involved in liver development, lipid metabolism and hepatitis C viral infection . Preclinical data have demonstrated that high miR‐122 elevations are observed in rodents given acetaminophen and beagle dogs given proprietary hepatotoxicants . This observation has been recapitulated in human studies.…”
Section: Promising New Dili Biomarkersmentioning
confidence: 87%
“…MiR‐122 is an miRNA that is found almost exclusively in the liver although in vitro data suggest that non‐hepatic cancerous cells can produce this miRNA as well . In vivo , miR‐122 makes up ~70% of the miRNA content in the liver, where it has been found to be involved in liver development, lipid metabolism and hepatitis C viral infection .…”
Section: Promising New Dili Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum ALT activity thus is the best screening test for CH. However, histopathologic evidence of CH can exist in the absence of increased serum liver enzyme activity . Increased serum alkaline phosphatase (ALP) activity occurs later in CH.…”
Section: Clincal Pathologymentioning
confidence: 99%
“…Less information is available regarding serum aspartate aminotransferase and GGT activities in CH, but they tend to mirror serum ALT and ALP activities, respectively, although both are less sensitive. Evidence suggests that serum concentrations of some microRNAs, particularly miR‐122, are increased with minimal liver injury in the dog in the absence of increases in ALT activity, and thus may have superior sensitivity over standard serum liver enzymology in detecting early CH …”
Section: Clincal Pathologymentioning
confidence: 99%